EVALUATION OF LEADERSHIP POLICY OF DEAN IN EFFORTS TO INCREASE READY-TO-USE GRADUATES (STUDY PROGRAM OF STUDENT CREATIVITY ANIMAL HUSBANDRY FACULTY OF BRAWIJYA UNIVERSITY): Lilik Sunatri - LILIK SUNARTI (JOURNAL AKSES STIA MALANG, 2019)
Abstract This study uses qualitative research aims to observe, to know, to observe social phenomena in a setting, as well as developing the concept in solving a problem, the data were collected by interview (a responsibility), supported by resource persons as needed research. Data analysis using interactive analysis model of Miles and Huberman that consists of data collection, the data display, data reduction and Conclusions; drawing/verifying policies to improve the quality of college graduates to someday have the academic ability to develop, apply and disseminate knowledge, technology  and creativity in the field of animal husbandry. Still, rare students who are interested and are interested in the program of student creativity. not a few who do not or do not want to take any chance that the CRP program, perhaps because students have not found meaning or benefit from the program, or students feel less time to learn, assumed to follow such activities are a waste of time. students can also just want to focus on activities in order to achieve IP college or high GPA. if such a fact, then there is a lot of students to be students butterfly (college tuition home- return). therefore, for the students, while in college is an opportunity to develop themselves, then try to take the opportunity offered by CRP. proved to be quite a lot of graduates who can compete in the world of work, to create jobs that are received at the enterprise, government, and private agencies as actively participating in the CRP program.  Keyword: leadership policy, graduates student, animal husbandry faculty